Why do healthcare workers refuse tuberculosis preventive treatment (TPT)? a qualitative study from Puducherry, South India - Palanivel Chinnakali; Sonali Sarkar; Sadhana Subramanian; Jilisha Gnanadhas; Manju Rajaram; Senbagavalli Prakashbabu (BMJ Open Respiratory Research)
Background The sustainable development goal (SDG) 3.3.2 prompted India to devise the National Strategic Plan 2017–2025, targeting tuberculosis (TB) eradication by 2030. The prevention pillar of this plan emphasises on Tuberculosis Preventive Treatment (TPT) for those with TB infection (TBI). Healthcare workers (HCWs), identified as one of the high-risk groups by the WHO, show a higher refusal rate for TPT. We aimed to explore the reasons for TPT refusal among the HCWs identified with TBI in Puducherry, South India during 2023.Methods A qualitative descriptive study was conducted among 12 HCWs from a publicly funded tertiary care hospital, each with at least 5 years of experience. Participants were selected by maximum variation sampling, based on the department of work, current TBI status and subject expertise. The in-depth interviews, guided by the health belief model, lasted approximately 45 min each. Two researchers performed manual thematic analysis using the mixed approach for coding. Codes were grouped into categories and themes. Discrepancies were resolved through discussion with a third researcher, reaching a consensus.Results Three overarching themes emerged: perceived threats, beliefs regarding health interventions and empowering factors. Perceived threat elucidated the lower perceived vulnerability of contracting TB and minimal chance for progression of TBI to TB disease despite having continuous exposure and uncertainties in the workplace. Beliefs about health interventions included perceived obstacles and advantages, such as testing challenges and lack of awareness, as well as the benefits of prophylaxis and infection control measures. Empowering factors centred on prompting action and self-confidence, highlighting strategies to encourage TBI testing through administrative actions and endorsing shorter treatment plans.Conclusions Addressing the identified knowledge gaps and false perception through targeted interventions, healthcare institutions can improve TPT uptake. Implementing a comprehensive strategy that combines hospital policies to initiate screening and treatment, a supportive environment and shorter TPT regimens is essential to prevent TB among HCWs.